Crosslinking of unsaturated polyester by conjugated soybean oil via Diels Alder reaction - Esen, Eren. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this study, unsaturated polyester (UPE) is crosslinked with conjugated soybean oil (CSO) with using the Diels Alder reaction and to prepare a one component UPE which can be cured in the mold simply by heating. The goal is to use a nontoxic and non-volatile reactive diluent for curing of UPE. Crosslinking reaction occurred between conjugated diene part of the CSO and the maleate double bonds of the UPE via the Diels Alder reaction. Because it was hard to predict the correct stoichiometry of the reaction, it was determined experimentally. The reaction conditions (reaction time and temperature) were determined by using CSO as a diene. The best reaction efficiency and high crosslinking density was obtained only by using trans,trans conjugated soybean oil (t-CSO). Without using any solvent or catalyst. t-CSO was obtained by the elaidinization of CSO. The effects of conjugation and conjugated double bond geometry were investigated by comparing natural soybean oil, CSO and t-CSO as a diene in the crosslinking reaction. Characterizations of products were done by FTIR and NMR spectroscopy and mechanical properties of UPE:t-CSO crosslinked products with different weight ratios of components were analyzed by surface hardness, compression and swelling tests. Mechanical tests showed that, with higher amount of UPE, relative crosslink density, surface hardness and compressive strength of products were increased. Cured UPE samples containing up to 50% renewable, plant oil based t-CSO were produced.
Keywords: Polyesters.; Diels-Alder reaction.